KONSEP MEMILIH PASANGAN IDEAL PERSPEKTIF PEMIKIRAN KH. M.iHASYIM iASY’ARI DALAM iKITAB iḌAW` iAL-MIŞBAḤ iFI BAYĀN iAHKĀM iAL-NIKĀH - Muhammad Qodafi; Abdullah Afif (JOURNAL SAINS STUDENT RESEARCH, 2024)
This article aims to explore the concept of an ideal soul mate according to KH's thoughts. M. Hasyim Asy'ari and his thinking methodology. This research is library research, carried out based on various data sources such as books, documents and literature that are relevant to the research topic. Data collection in this research used documentation methods, while the data analysis technique applied was descriptive analysis. From this research, it was concluded that KH. M. Hasyim Asy'ari in his book argues that the criteria for selecting an ideal partner are in accordance with the words of the Prophet who stated that women are married for four things: beauty, lineage, wealth and religion. However, ithe most important thing according to the Prophet SAW is religion, because religion is the main goal in choosing a partner. In the book Dhoul Misbah, KH. M. Hasyim Asy'ari uses the Qouly method, namely a method of exploring law by studying existing problems and looking for answers in the schools of Islamic jurisprudence books, or in other words, following opinions that already exist within the scope of a particular school of thought.